2013
DOI: 10.1007/s12237-013-9591-6
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size-Dependent Effects of Solar UV Radiation on Primary Production in Coastal Waters of the South China Sea

Abstract: In order to examine the effects of solar ultraviolet radiation (UVR, 280-400 nm) on photosynthesis of differently cell-sized phytoplankton, natural phytoplankton assemblages from the coastal waters of the South China Sea were separated into three groups (>20, 5-20, and <5 μm) and exposed to four different solar UV spectral regimes, i.e., 280-700 nm (PAR + UVR), 400-700 nm (PAR), 280-400 nm (UV-A+B), and 315-400 nm (UV-A). In situ carbon fixation measurements revealed that microplankton (>20 μm) efficiently uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Likewise, the vulnerability of microalgae to UVR damage may be dependent on cell size, which determines light absorption properties (Agustí, 1991). Photosynthetic carbon fixation of small phytoplankton species was reported to be much more sensitive to UVB radiation than that of large species in a coastal ecosystem (Li and Gao, 2013), and a recent laboratory study also revealed that the UVB sensitivity of diatoms decreased with increasing cell size (Wu et al, 2015). Small cells are also vulnerable to the accumulation of cyclobutane pyrimidine dimers but photosynthesis is less inhibited by UVB radiation, which may be caused by faster photo-repair in small cells (Buma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the vulnerability of microalgae to UVR damage may be dependent on cell size, which determines light absorption properties (Agustí, 1991). Photosynthetic carbon fixation of small phytoplankton species was reported to be much more sensitive to UVB radiation than that of large species in a coastal ecosystem (Li and Gao, 2013), and a recent laboratory study also revealed that the UVB sensitivity of diatoms decreased with increasing cell size (Wu et al, 2015). Small cells are also vulnerable to the accumulation of cyclobutane pyrimidine dimers but photosynthesis is less inhibited by UVB radiation, which may be caused by faster photo-repair in small cells (Buma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…UVR can decrease phytoplankton growth and photosynthesis as well as nutrients uptake (Sobrino et al 2004, Gao et al 2007a, Korbee et al 2010, harm DNA or protein molecules (Roy 2000, Wei et al 2004 and even lead to cell death (Agustí and Llabrés 2007), and therefore, can alter community structures (Marcoval et al 2008, Beardall et al 2009). On the other hand, longer UV-A wavebands (320-400 nm) are known to function in photorepairing the UV-B induced damages to DNA (Buma et al 2003), trigger chlorophyll fluorescence (Halldal 1967) and energize the photosynthesis of coastal phytoplankton assemblages (Helbling et al 2003, Mengelt and Prézelin 2005, Gao et al 2007b, Li and Gao 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton species (especially those in the upper mixing layer), while utilizing light energy for photosynthesis, are also exposed to UVR that is known to reduce their growth, photosynthesis and calcification, damage DNA or D1 protein and pigments (Helbling et al 1992, Buma et al 2003, Bouchard et al 2005, Gao et al 2009. Moderate levels of UV radiation A (UVA, 315-400 nm) also have positive effects, such as photo-repair of UV radiation B (UVB)-damaged DNA (Buma et al 2003) and stimulate photosynthetic CO 2 -fixation at low photosynthetically active radiation (PAR) (Mengelt andPrézelin 2005, Li et al 2011) or at PAR absence conditions (Gao et al 2007, Li andGao 2013). Mixing that moves phytoplankton up and down the water column causes fluctuation of the levels of solar radiation, enhancing non-photochemical quenching (Milligan et al 2012) and lowering synthesis of UV-screening compounds (e.g., mycosporine-like amino acids [MAAs]) (Hernando et al 2006), and also mitigating the negative effects of UVR (Neale et al 1998).…”
Section: Environmental Measurementsmentioning
confidence: 99%
“…Following this insight, extensive studies were conducted on these coral reefs (e.g., Li et al 2008, Dong et al 2009, Huang et al 2011, Hughes et al 2012; however, rather less attention was paid to phytoplankton in these coral reef waters (Zhang et al 2009, Shen et al 2010, Li and Gao 2013. As a habitat sharing counterpart to corals, phytoplankton may indirectly affect the survival of corals (discussed earlier); in view of this point, it is essential to evaluate the physiological effects of environments on these organisms.…”
Section: Environmental Measurementsmentioning
confidence: 99%